The Development of the Creative Industries to Create a Competitive Advantage: Studies in Small Business Sector - Sasongko, Totok; Rifa’i, Mohamad; Sayekti, Nugraheni Suci (Journal of Economic Development, Environment and People, 2019)
Nowadays, developing creative industries is one of the main priority of Indonesia’s economic development plans. The government have been conducting many efforts to push the development of creative industries in Indonesia such as discussion with policy makers in the field of creative economic development and in all regions and giving incentives and easy access to investors who want to invest their money in creative industries. Long term goal of this study is to formulate a theory of the development of basic model of creative industry entrepreneurs capable of creating added value on the creative industrial products that have been produced. The added value is very necessary because it will be able to help raise the value of the resulting product and have the competitiveness to attract consumer interest and win the competition in the market so that this creative industries can continue to grow are sustained. Demonstrating the results of the study in order to develop the necessary creative economic collaboration between the different actors that play a role in the creative industry, community, business world, as well as the government which is a fundamental prerequisite. The third element of the collaboration without the feared economic development creative will not run in accordance with the program that has been prepared by the government because of possible disharmony in the implementation of the development of economic activities creative.